Reframing Anti-Bullying Policies Through Maqāṣid al-Sharīʿah: Psychological Protection and Children's Rights in Indonesian Education - Afif Alfiyanto; M. Ikhwan; Syatria Adymas Pranajaya; Randi Muhammad Gumilang; Gusti Gusti (Perkumpulan Dosen Tarbiyah Islam, Indonesia, 2026)
School bullying in Indonesia represents a severe public health crisis, with prevalence rates exceeding 41% and ranking fifth globally. Despite robust regulatory frameworks, a critical research gap persists: existing anti-bullying policies remain predominantly procedural, lacking systematic integration of Islamic ethical-religious principles essential for psychological protection and moral development. This study addresses this gap by examining the alignment of Indonesia's anti-bullying regulations with Islamic legal principles on children's rights. Introducing methodological novelty, the research operationalizes Maqāṣid al-Sharīʿah objectives—specifically ḥifẓ al-nafs (preservation of psychological well-being) and ḥifẓ al-ʿaql (protection of cognitive development)—as explicit evaluative criteria for national policy analysis, bridging trauma-informed psychology with classical Islamic jurisprudence for the first time in this domain. Employing a normative-juridical approach integrated with socio-legal analysis, the study evaluates Islamic sources, statutory instruments, and institutional reports from 2020–2026. Findings reveal normative convergence between national policies and Islamic principles regarding child protection, yet significant implementation gaps persist due to administrative orientations neglecting moral-spiritual dimensions. Bullying inflicts severe psychological harm, with 66% of victims exhibiting PTSD-compatible symptoms, which current policies inadequately address. The study proposes a Humanistic-Islamic Anti-Bullying Policy Integration framework comprising six interconnected pillars. Theoretically, this research advances Islamic legal discourse by expanding Maqāṣid theory beyond traditional juridical domains into contemporary educational policy design, demonstrating its capacity to operationalize psychological protection within a holistic, values-based paradigm. This model offers policymakers a culturally resonant, ethically grounded approach to bullying prevention in Muslim-majority contexts.